2017
DOI: 10.1128/aem.03236-16
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptional Responses to Osmotic, Oxidative, and Imipenem Stress Conditions in Pseudomonas putida

Abstract: Bacteria cope with and adapt to stress by modulating gene expression in response to specific environmental cues. In this study, the transcriptional response of KT2440 to osmotic, oxidative, and imipenem stress conditions at two time points was investigated via identification of differentially expressed mRNAs and small RNAs (sRNAs). A total of 440 sRNA transcripts were detected, of which 10% correspond to previously annotated sRNAs, 40% to novel intergenic transcripts, and 50% to novel transcripts antisense to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 95 publications
7
39
0
Order By: Relevance
“…A recent report indicates that the salt concentration is dependent on motility in a pigment halotolerant Vibrio strain isolated from Salar de Atacama, but motility was inhibited in higher salt concentrations (150 g/l NaCl; Gallardo et al, 2016 ). Substantial energy is needed for flagellar biosynthesis and bacteria are able to inhibit certain processes in response to stress, motility was reduced, and biofilm formation was seen in SH31 ( Figure 4 ) a general bacterial response to osmotic stress found in diverse organisms, as it was shown in Pseudomonas putida ( Bojanovič et al, 2017 ). Some factors that induce biofilm maturation, including in Pseudomonas and Shewanella , are changes in oxygen or carbon substrate concentration, pH, or other chemical parameters ( Gjermansen et al, 2005 ).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…A recent report indicates that the salt concentration is dependent on motility in a pigment halotolerant Vibrio strain isolated from Salar de Atacama, but motility was inhibited in higher salt concentrations (150 g/l NaCl; Gallardo et al, 2016 ). Substantial energy is needed for flagellar biosynthesis and bacteria are able to inhibit certain processes in response to stress, motility was reduced, and biofilm formation was seen in SH31 ( Figure 4 ) a general bacterial response to osmotic stress found in diverse organisms, as it was shown in Pseudomonas putida ( Bojanovič et al, 2017 ). Some factors that induce biofilm maturation, including in Pseudomonas and Shewanella , are changes in oxygen or carbon substrate concentration, pH, or other chemical parameters ( Gjermansen et al, 2005 ).…”
Section: Discussionmentioning
confidence: 87%
“…Finally, genes related to biofilm ( pgaC ), cell chemotaxis ( bdlA ), and signaling ( luxS ) were induced in the NaCl conditions; on the contrary, ywqC or tkm (capsule/biofilm) was found to be significantly decreased in the 25 g/l condition and was not changed in 50 g/l of NaCl. It has been found that many of the reactions related to biofilm formation are upregulated in response to salinity ( Bojanovič et al, 2017 ). LuxS is a signaling protein that mediates quorum sensing between certain species, as well as biofilm formation and motility.…”
Section: Discussionmentioning
confidence: 99%
“…The low‐irradiation community, when exposed to high light, rapidly showed gene shifts that were reflective of the community changes due to environmental stress. We especially detected an increase in abundance of genes related to osmotic stress, which tend to be accompanied by reactions related to oxidative stress in bacterial cells (Botsford and Lewis, ; Bojanovič et al ., ). Genes related to the biosynthesis of compounds such as glutathione that can hamper oxidative damage under osmotic stress (Smirnova and Oktyabrsky, ), and ergothioneine, an amino acid with antioxidant and cytoprotective capabilities against cellular stressors (Cheah and Halliwell, ), were also detected in increased abundances.…”
Section: Discussionmentioning
confidence: 99%
“…Such profiles not only expose global physiological responses, but also pinpoint the roles of distinct genes that can then be separately studied. Without surprise, Pseudomonas putida has not been alien to such technical and conceptual developments and a suite of transcriptomes of this bacterium have been published in recent years with different methods for inspecting the responses of this microorganism to different physicochemical settings (Yuste et al ., ; Kim et al ., , ; La Rosa et al ., ; Bojanovic et al ., ; Molina‐Santiago et al ., ). However, such experiments were run by different laboratories with diverse RNA extraction and preparation methods, and with different data analysis and representation tools, and thus make comparisons challenging.…”
Section: Introductionmentioning
confidence: 99%